Problematika Pengelolaan Penyelenggaraan Umrah di Kota Surakarta - Akhmad Anwar Dani (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2018)
ABSTRACTThis article focuses on mapping the problems that arise in the implementation of umrah worship in the city of Surakarta either on the side of the Ministry of Religious Affairs as regulators, Umrah pilgrim travel agencies as the Umrah Pilgrimage Pilgrim (PPIHU) and Umrah pilgrims as consumers. Using the descriptive qualitative method it is found that the problems that arise in each involved party are interrelated with one another. The most fundamental problem and trigger the emergence of other problems is the unclear regulation of the management of Umrah worship at the Ministry of Religious Affairs at District or city level.ABSTRAKArtikel ini fokus pada pemetaan masalah-masalah yang muncul dalam penyelenggaraan ibadah umrah di kota Surakarta baik pada sisi Kementerian Agama selaku regulator, biro perjalanan haji umrah sebagai Penyelenggara Perjalanan Ibadah Haji Umrah (PPIHU) dan jamaah umrah sebagai konsumen. Dengan menggunakan metode kualitatif deskriptif ditemukan bahwa masalah yang muncul pada setiap pihak yang terlibat saling terkait antara satu dengan yang lain. Masalah yang paling mendasar dan memicu munculnya masalah yang lain adalah belum jelasnya regulasi pengelolaan ibadah umrah pada Kementerian Agama di tingkat Kabupaten / Kota.